Once versus three times daily dosing of oral budesonide for active Crohn's disease: A double-blind, double-dummy, randomised trial. (1st September 2014) - Dignass, Axel; Stoynov, Simeon; Dorofeyev, Andrey E.; Grigorieva, Galina A.; Tomsová, Eva; Altorjay, István; Tuculanu, Daniel; Bunganič, Ivan; Pokrotnieks, Juris; Kupčinskas, Limas; Dilger, Karin; Greinwald, Roland; et al.
Abstract: Background: Oral budesonide 9 mg/day represents first-line treatment of mild-to-moderately active ileocolonic Crohn's disease. However, there is no precise recommendation for budesonide dosing due to lack of comparative data. A once-daily (OD) 9 mg dose may improve adherence and thereby efficacy. Methods: An eight-week, double-blind, double-dummy randomised trial compared budesonide 9 mg OD versus 3 mg three-times daily (TID) in patients with mild-to-moderately active ileocolonic Crohn's disease. Primary endpoint was clinical remission defined as CDAI < 150 at week 8 (last observation carried forward). Results: The final intent-to-treat population comprised 471 patients (238 [9 mg OD], 233 [3 mg TID]). The confirmatory population for the primary endpoint analysis was the interim per protocol population (n = 377; 188 [9 mg OD], 189 [3 mg TID]), in which the primary endpoint was statistically non-inferior with budesonide 9 mg OD versus 3 mg TID. Clinical remission was achieved in 71.3% versus 75.1%, a difference of − 3.9% (95% CI [− 14.6%; 6.4%]; p = 0.020 for non-inferiority). The mean (SD) time to remission was 21.9 (13.8) days versus 21.4 (14.6) days with budesonide 9 mg OD versus 3 mg TID, respectively. In a subpopulation of 122 patients with baseline SES-CD ulcer score ≥ 1, complete mucosal healing occurred in 32.8% (21/64) on 9 mg OD and 41.4% (24/58) on 3 mg TID; deep remission (mucosal healing and clinical remission) was observed in 26.6% (17/64) and 32.8% (19/58) of patients, respectively. Treatment-emergent suspected adverse drug reactions were reported in 4.6% of 9 mg OD and 4.7% of 3 mg TID patients. Conclusions: Budesonide at the recommended dose of 9 mg/day can be administered OD without impaired efficacy and safety compared to 3 mg TID dosing in mild-to-moderately active Crohn's disease.